2015
DOI: 10.1002/chem.201501232
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Olefination of Anilides with Unactivated Alkenes Catalyzed by an (Electron‐Deficient η5‐Cyclopentadienyl)Rhodium(III) Complex Under Ambient Conditions

Abstract: The oxidative olefination of sp(2) C-H bonds of anilides with both activated and unactivated alkenes using an (electron-deficient η(5) -cyclopentadienyl)rhodium(III) complex is reported. In contrast to reactions using this electron-deficient rhodium(III) catalyst, [Cp*RhCl2 ]2 showed no activity against olefination with unactivated alkenes. In addition, the deuterium kinetic isotope effect (DKIE) study revealed that the C-H bond cleavage step is thought to be the turnover-limiting step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(20 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…In our previous reports, electron‐deficient Cp E Rh III and amide‐pendant Cp A Rh III complexes showed high catalytic activity toward the ortho ‐C−H bond functionalization of electron‐rich anilides . We anticipated that these Rh III complexes would show high catalytic activity towards the ortho ‐C−H bond bromination of O‐phenyl carbamates due to their electron‐rich nature.…”
Section: Methodsmentioning
confidence: 92%
“…In our previous reports, electron‐deficient Cp E Rh III and amide‐pendant Cp A Rh III complexes showed high catalytic activity toward the ortho ‐C−H bond functionalization of electron‐rich anilides . We anticipated that these Rh III complexes would show high catalytic activity towards the ortho ‐C−H bond bromination of O‐phenyl carbamates due to their electron‐rich nature.…”
Section: Methodsmentioning
confidence: 92%
“…In 2015, Tanaka and co‐workers developed an electron‐deficient‐rhodium‐catalyzed method for oxidative olefination with unactivated olefins and N ‐acetyl anilides . The precatalyst – an ethoxycarbonyl‐substituted cyclopentadienyl‐Rh III [{Cp*RhCl 2 } 2 ] complex developed by the same group – was found to be effective for these olefination reaction at room temperature.…”
Section: Linear‐selective Olefinationmentioning
confidence: 99%
“…Interest in olefin coupling reactions, such as oxidative olefination and related olefinic homo‐ and cross‐coupling reactions that are predicated on the activation of alkenyl CH bonds, continues to grow. In recent studies, we have found that the square pyramidal pentaruthenium cluster complex [Ru 5 (µ 5 ‐C)(CO) 15 ] ( 1 ) is able to activate the formyl CH bond in dimethylformamide by a cluster‐opening C–H oxidative addition to the Ru 5 cluster with formation of a bridging formamido ligand [Equation (1)] …”
Section: Introductionmentioning
confidence: 99%